An improved risk and reliability framework-based maintenance planning for food processing systems. Issue 2 (4th March 2023) - Soltanali, Hamzeh; Khojastehpour, Mehdi; Torres Farinha, José
ABSTRACT: In food processing systems, it is necessary to evaluate the risk process and reliability in order to prevent unexpected events and control functional safety through well-planned maintenance. This study examines risk and reliability models and develops their theories using a novel framework based on failure behavior trends. The proposed framework was implemented in edible oil industries, specifically purification processes, and consists of three steps: first, identifying potential failures using risk-based approaches such as Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA); second, adapting a statistical structure consisting of homogenization survey and validity of identity and independence; and finally, estimating the failure rate and reliability to find the suitable maintenance intervals. The findings revealed that the proposed framework is capable of identifying critical equipment with high failure rates as the most important bottlenecks in edible oil processing lines, allowing maintenance plans to be carried out based on the various levels of reliability. Furthermore, opportunistic maintenance intervals were suggested due to the series configuration of equipment in such a process. As a result, the findings of this study may be useful in improving process safety and availability in the food processing industry.